2016
DOI: 10.1089/ars.2016.6739
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Flash: Integrative Reactive Oxygen Species and pH Signals in Cell and Organelle Biology

Abstract: Significance: Recent breakthroughs in mitochondrial research have advanced, reshaped, and revolutionized our view of the role of mitochondria in health and disease. These discoveries include the development of novel tools to probe mitochondrial biology, the molecular identification of mitochondrial functional proteins, and the emergence of new concepts and mechanisms in mitochondrial function regulation. The discovery of “mitochondrial flash” activity has provided unique insights not only into real-time visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 90 publications
(260 reference statements)
2
54
0
Order By: Relevance
“…Are pH and ROS flicker 63 related to membrane potential flicker? Recent work has shown that, in addition to membrane potential flicker (measured via TMRE), pH may also flicker and the mitochondria release “pufs” or ROS.…”
Section: Figurementioning
confidence: 99%
“…Are pH and ROS flicker 63 related to membrane potential flicker? Recent work has shown that, in addition to membrane potential flicker (measured via TMRE), pH may also flicker and the mitochondria release “pufs” or ROS.…”
Section: Figurementioning
confidence: 99%
“…In addition, physiological and pathological perturbations, such as metabolic substrates [16, 20], electrical stimulation [17, 21], Ca 2+ [28, 49], ischemic-reperfusion [10, 43], insulin resistance [18], and mitochondrial stresses [20, 48], also modulate mitochondrial flash frequency. Taken together, increasing evidence suggests that mitochondrial flash is a composite biomarker that integrates mitochondrial functions including respiration, ROS production, pH regulation and mPTP opening [50]. Thus, monitoring this single mitochondrial event is a useful tool for studying the role of individual mitochondria in cell signaling, function and dysfunction [50].…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, increasing evidence suggests that mitochondrial flash is a composite biomarker that integrates mitochondrial functions including respiration, ROS production, pH regulation and mPTP opening [50]. Thus, monitoring this single mitochondrial event is a useful tool for studying the role of individual mitochondria in cell signaling, function and dysfunction [50]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations